Kajian Tentang Struktur Organisasi Tata Kerja Badan Perencanaan Pembangunan Daerah di Propinsi Jawa Tengah - Suwitri, Sri (Jurnal Aplikasi Manajemen, 2008)
Change of Public Administration Science from Traditional Public Administration to New Public Management (NPM). encourage the Indonesian central government transfer the power to the local government. Decentralization in Indonesia has been accomodated in Law Number 5/1974, Law Number 22/1999 and Law Number 32/2004. The Law Number 32/ 2004 is followed by Government Regulation of Republic Indonesia Number 41/2007 placed planning authority in the hands of BAPPEDA (Planning Development Bourd). Due to this, there are also changes in the Planning Development Boards in municipal and regencial government in Central Java by changing their administration and organizational chart (SOTK).